Predictive Efficacy of Haematological Biomarkers in COVID-19 infection - Nadeem Ikram,Asma Nafisa, Rabia Anjum,Naeem Akhter, Nadeem Ikram,Asma Nafisa, Rabia Anjum,Naeem Akhter (Journal of Rawalpindi Medical College, 2020)
Introduction: The ongoing Corona Virus Pandemic is linked with high rates of morbidity and mortality globally. Early and effective predictors of clinical outcomes are urgently required to develop effective management protocols. Objective: To investigate the predictive efficacy of haematological biomarkers in Covid -19 infection Methods: Blood samples were drawn from COVID‐19 infected pneumonia patients. Baseline clinical information was collected and quantification of hemostatic variable was done. Laboratory data both groups expired and recovered were compared using t- test, Mann Whitney- U test, chi squared-test and Kruskal Wallis test. Multivariate regression analysis was performed to determine the independent contribution of haematological variable in Covid19 related mortality. Receiver operating characteristic curve were drawn to find the predictive efficacy of significantly related parameters. Results: Out of 191 patients 68.1% were male. D‐dimer (median 800 ng/mL; IQR 200‐3200) and NLR (median 10.40; IQR 3.20-22.80) were found to be predominantly raised and significantly correlated with Covid mortality in multivariate regression analysis. The optimum cutoff value of D-dimer to predict in-hospital mortality was 450 ng/ml with a sensitivity of 71.6% and a specificity of 95.8%. The optimum cutoff value of NLR to predict in-hospital mortality was 5.450 with a sensitivity of 70.1% and a specificity of 71%. Conclusion: D-dimer and NLR could be used as the signiﬁcant indicators in predicting the mortality of COVID-19.